Potential Hematological Predictors Assessing Severity in Patients Presenting with Dengue - Maria Sattar, Zuha Ali, Nadia Kashif, Shahida Mushtaq, Ambreen Zafar, Nazia Siddiqui (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the potential hematological predictors and biochemical markers for assessing severity in patients presenting with dengue Methods: This descriptive study was conducted at Jinnah Medical College/ District Specialist Naseerullah Babar Memorial Hospital, Peshawar in the duration from March, 2022 to August, 2022 on 150 Dengue NS1 (ICT) positive patients. Hematological and biochemical markers were assessed among severe vs non-severe dengue fever patients. Hematological and biochemical markers were assessed by T-test with P < 0.05 as significant. Results: Hematocrit (%), AST (U/L) and ALT (U/L) levels were higher significantly in the severe dengue patients’ vs non-severe dengue fever patients, platelet (mcL) and White blood cells (mcL) were significantly lower in the severe dengue patients’ vs non-severe dengue fever patients. Conclusion: We conclude that Hematocrit (%), platelets count, White blood cells, Alanine transaminase (ALT) (U/L) and Aspartate aminotransferase (AST) (U/L) and are important hematological and biochemical predictors for assessing the severity of dengue. Keywords: Hematological markers, Biochemical markers, Dengue fever, Severity